3D Printed Materials Dentistry - Becker, Kathrin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue reprint covers a wide range of applications of 3D-printing in dentistry. Five out of eleven research papers deal with applications of 3D printing in orthodontics, one study presents a 3D-printed fitting system for the FFP2 that were applied during the COVID-19 pandemic, and the others address applications in prosthodontics and restorative dentistry.